The Effect of Public Facilities on the Quality of Life in the Simarito Slum in Simarito Village, West Siantar District, Pematang Siantar City - Umar Juni Dalimunthe; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to examine the Influence of Public Facilities on the Quality of Life in the Simarito Slum in Simarito Village, West Siantar District, Pematang Siantar City. Qualitative research methods aim to understand social phenomena from the perspective of the individuals involved and focus on the context and meaning behind their experiences. In this study, interviews can be conducted with local residents to understand their experiences regarding public facilities and their impact on quality of life. The qualitative research method described above aims to understand the influence of public facilities on the quality of life of people in the Simarito slum. Research results Overall, public facilities have a crucial role in improving the quality of life of the community in the Simarito Slum Area. While the challenges in their provision and maintenance are quite complex, collaborative efforts between governments, communities, and other stakeholders can lead to significant improvements. This research shows that to achieve a sustainable improvement in the quality of life of the community, it is important to integrate the community's perspective in every stage of planning and maintenance of public facilities.